STUDENTSâ VOCABULARY ACHIEVEMENT BY USING LIST GROUP LABEL - Junaid, Junaid (Lembaga Perpustakaan Unismuh Makassar, 2012)
The research aimed to find out the improvement of the studentsâ vocabulary mastery by List Group Label (LGL) at the first year students of SMP Nasional Makassar in 2011/2012 Academic Year. The researcher used a classroom action research method with cycle I and cycle II design, where each cycle consisted of four meetings. It employed vocabulary test instrument. A number of subjects of the research were 25 students in the first year class. They consisted of 12 women and 13 men. The research took real data from the school to know the studentsâ vocabulary mastery. The research findings indicated that using List Group Label (LGL) could improve the studentsâ nouns from cycle I to cycle II, where as in cycle I the studentsâ achievement in nouns was 57.70%, but after evaluation in cycle II the studentsâ nouns became 73.80%. On the other hand the studentsâ verbs developed too from cycle I to cycle II, where in cycle I the studentsâ achievement in verbs was 57.60%, but after evaluation in cycle II the studentsâ verbs became 74.60%. The findings indicated that there was improvement in the studentsâ vocabulary mastery from cycle I to cycle II, where in cycle I the studentsâ vocabulary mastery was 57.70%, but after evaluation in cycle II the studentsâ vocabulary mastery became 74.20%. While the standard targeted achievement was 62%.Keywords: Vocabulary, Achievement, List Group Label.Penelitian ini bertujuan untuk mengetahui peningkatan penguasaan kosakata siswa dengan Daftar Kelompok Label (LGL) pada siswa tahun pertama SMP Nasional Makassar di 2011/2012 Tahun Akademik. Peneliti menggunakan metode penelitian tindakan kelas dengan siklus I dan desain siklus II, di mana setiap siklus terdiri dari empat pertemuan. Penelitian ini menggunakan instrumen tes kosakata. Jumlah subyek penelitian adalah 25 siswa di kelas tahun pertama. Mereka terdiri dari 12 perempuan dan 13 laki-laki. Penelitian ini mengambil data ril dari sekolah untuk mengetahui penguasaan kosakata siswa. Temuan penelitian menunjukkan bahwa dengan menggunakan Daftar Kelompok Label (LGL) dapat meningkatkan kata benda dari siklus I ke siklus II, dimana pada siklus I siswa nomina prestasi siswa adalah 57, 70%, tapi setelah evaluasi pada siklus II nomina siswa menjadi 73, 80%. Di sisi lain kosakata kata kerja siswa dikembangkan juga dari siklus I ke siklus II, di mana pada siklus I siswa berprestasi di Kosakata kata kerja adalah 57, 60%, tapi setelah evaluasi pada siklus II kosakata kata kerja siswa menjadi 74, 60%. Temuan menunjukkan bahwa ada peningkatan siswa penguasaan kosakata dari siklus I ke siklus II, dimana pada siklus I siswa penguasaan kosakata adalah 57, 70%, tapi setelah evaluasi pada siklus II penguasaan kosakata siswa menjadi 74, 20%. Sementara standar yang ditargetkan pencapaian adalah 62%.Kata Kunci: Kosakata, Prestasi, Daftar Grup Label.